TUTORIAL PRA-KELAS: SEBUAH STRATEGI PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA PERKULIAHAN FISIKA DASAR - Saepuzaman, Duden; Sriyansyah, Syakti Perdana; Karim, Saeful; Sari, Ika Mustika (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
The Pre-Class Tutorial have been implemented to improve conceptual understanding of basic physics concepts among the pre-service physics teacher at one of Education College in Bandung City. This study was motivated by the previous research findings that students encounter the conceptual difficulties and the lack of understanding in introductory physics course. Based on these findings, we developed pre-class tutorial that facilitate students either to construct their own concepts o rto apply the concepts. The descriptive method was used to 260 third-years students of Physics Education Department. The increasing of conceptual understanding was identified from the average score of studentsâ achievement on the exam test. The findings showed that the use of pre-class tutorial effectively improve studentsâ conceptual understanding.